Successful reversal of delayed spinal cord ischemia complicating thoracic endovascular aortic repair for type B aortic dissection with hemodynamic optimization and insertion of a lumbar spine drain: a case report. - Mafdy N. Basta (Critical Care Innovations)
Aortic dissection is caused by an intimal tear that results in high-pressure flow of blood between the layers of the aorta, creating true and false lumens. The more widely used Stanford system classifies aortic dissections into type A (involves the ascending aorta) or type B (all other dissections). Complicated type B aortic dissection requires urgent surgical or endovascular intervention. Spinal cord ischemia remains a devastating complication that could happen after both open and endovascular aortic repair. The following case is a 53-year-old man who underwent endovascular repair for complicated type B aortic dissection. His postoperative course was complicated by spinal cord ischemia (paraparesis) that presented on postoperative day 2. Spinal cord ischemia was successfully reversed by prompt recognition and treatment, including cerebrospinal fluid drainage and mean arterial blood pressure augmentation. This case discusses the evolving role of endovascular repair for thoracic aortic dissection, highlights the risk factors for spinal cord ischemia, and emphasizes the importance of close postoperative monitoring and prompt applications of protocols, including cerebrospinal fluid drainage, for early detection and possibly reversal of the devastating complication of spinal cord ischemia.